Leer a Semprún, los límites entre la literatura en estado puro y la literatura ancilar: la supervivencia del escritor, el arte y su memoria (2016)
This reflection aims to present the results of the analysis of some discursive, literary and creative boundaries that come together in La escritura o la vida (1995) by Jorge Semprun; to this end, the contemplated literary-critical method here will concentrate on observing three thematic boundaries: the first deals with establishing the ancillary literature present in this narrative, according to the statements made by the literary critic Alfonso Reyes in his work El deslinde (1944); the second explores the aesthetic and lessons of literary creation for writing conflicts present in this story, and finally, the third focuses on a brief examination of writing as a therapeutic exercise and resilient, from receipt of a distant Latin American reader. Thus, this argument is emerging as an analytical approach to the work of this Spanish writer.